Phytochemicals and Anti-Inflammatory Activity of Melicope Ptelefolia Champ Ex Benth - Suryati (2005)
Leaves of Melicope ptelefolia Champ ex Benth were examined for phytochemicals. Using various chromatography techniques such as normal column chromatography, gel filtration on sephadex LH-20 and radial chromatography seven compounds were isolated namely, kokusaginine (94), p-sitosterol (llo), p-0-geranylcoumaric acid (102), 3- geranyl-2,4,6-trihydroxyacetophenone (1 1 I), the tentatively assigned compound benzopyranone (1 12), 4',5-dihydroxy-3,3',7-trimethoxyflavone (1 13) and scoparone (86). 3-Geranyl-2,4,6-trihydroxyacetophenonew as identified as a new natural product, which was previously reported as a synthetic compound. Nitric oxide (NO) inhibitory assay using RAW 246.7 murine monocytic macrophage and soybean lipoxygenase inhibitory assay were carried out in the primary screening of the crude methanolic extract, the hexane, dichloromethane and ethyl acetate fractions. Both the hexane and dichloromethane fractions were shown strongly to inhibit nitric oxide production with an ICso of 27.8 1 pglml and 34.13 pg/ml respectively. Meanwhile, inhibition of soybean lipoxygenase activity was shown only by the dichloromethane fraction at ICso 48.0 1 pg/ml Further anti-inflammatory investigation on the isolated compounds showed that kokusaginine significantly inhibited NO production with an ICso of 12.09 pglml (46.69 pM), while 3-geranyl-2,4,6-trihydroxyacetophenone inhibited formation of (9Z, 11E)- (1 39-1 3-hydroxyoctadeca-9,ll -dienoate with an ICsO of 7.35 pglml(24.17 pM). 3-Geranyl-2,4,6-trihydroxyacetophenone was further evaluated towards inhibition of cysteinyl leukotriene (CysLTs) production. The result showed that this compound significantly inhibited the production of CysLTs with an ICso of 12.13 pM. This was slightly lower than the ICso of nordihydroguaretic acid (8.13 pM) which was used as the reference drug.